The Return to 1975 and Some Aspects of the Built Environment Analysis Discipline & Methodology : The Thiberg Triangle and Beyond (Revisiting the ideas from 1999) - Haas, Tigran (Technium Social Sciences Journal, 2020)
Each reader will most probably come into this topic with hers/his professional background, different perceptions and view of things, understandings, expectations, etc. Given the incredible depth of the subject, but at the same time wishing to be approachable and ‘user-friendly’ to the reader, the paper will demonstrate a particular way of seeing the built environment. What will come out between and behind lines is multidisciplinary and systemic view as a conditio sine qua non of viewing this field as well as an approach, which tries to integrate different issues. The paper will also try to debate, bring out and question things as well as problematize around these issues. Its purpose is not to bring solutions, give answers or put up new theories or models. It will nonetheless have to give some suggestions and try to look at some things differently, especially where some postulates, definitions and outlook on things are fuzzy, hazy or unclear and based on false premises and undefined concepts. The main focus is to show that “faulty” models (defective and contradictory concept and categories and prepositions) can have disastrous consequences for the development of a certain discipline. As Norman Crowe pointed, ‘such is the nature of this subject that any discussion of it can be neither complete nor conclusively definitive.